Exponential Growth of Solutions with $L_{p}$-Norm of a Klein-Gordon Wave Equation with Strong Damping, Source and Delay Terms - Yazid, Fares; Ouchenane, Djamel (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we are investigating to figure out the exponential growth of solutions with $L_{p}$-norm of a viscoelastic Klein-Gordon wave equation with strong damping, source and delay terms.